1999
DOI: 10.1161/01.cir.100.8.813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Autonomic Neuropathy on Coronary Blood Flow in Patients With Diabetes Mellitus

Abstract: Diabetic autonomic neuropathy is associated with an impaired vasodilator response of coronary resistance vessels to increased sympathetic stimulation, which is related to the degree of SND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
153
3
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(175 citation statements)
references
References 31 publications
(41 reference statements)
12
153
3
7
Order By: Relevance
“…In previous studies, coronary vasoreactivity has been found to be either normal [28] or more frequently decreased [8,29,30,31,32] in diabetic patients. However, most of the previous studies have included patients with both Type 1 and Type 2 diabetes or other potentially confounding factors such as diabetic complications, smoking, hypertension, obesity and lipid abnormalities, which are known to further reduce coronary vasoreactivity.…”
Section: Discussionmentioning
confidence: 91%
“…In previous studies, coronary vasoreactivity has been found to be either normal [28] or more frequently decreased [8,29,30,31,32] in diabetic patients. However, most of the previous studies have included patients with both Type 1 and Type 2 diabetes or other potentially confounding factors such as diabetic complications, smoking, hypertension, obesity and lipid abnormalities, which are known to further reduce coronary vasoreactivity.…”
Section: Discussionmentioning
confidence: 91%
“…Similar problems are faced when comparing patients with silent myocardial ischaemia or infarction with healthy subjects. Increased heart rate and reduced heart rate variability, the hallmarks of diabetic autonomic neuropathy, seem to be associated with the rapid progression of coronary atherosclerosis [71], and tachycardia together with impairment of coronary blood flow and blood pressure regulation could help to precipitate attacks of myocardial ischaemia and contribute to its silent incidence in susceptible patients [72].…”
Section: Confounding Factorsmentioning
confidence: 99%
“…Dipyridamole or adenosine are applied to pharmacologically induce maximum coronary vasodilatation [111]. The cold pressor test assesses myocardial blood flow in response to sympathetic nerve stimulation [113].…”
Section: Coronary Blood Flow Reservementioning
confidence: 99%